Role of CD38 in Adipose Tissue: Tuning Coenzyme Availability? - Andrea Benzi (MDPI AG, 2021)
Nicotinamide adenine dinucleotide (NAD+) is a fundamental molecule in the regulation of energy metabolism, representing both a coenzyme and a substrate for different NAD+ degrading enzymes. Among these enzymes, CD38 can be seen under two perspectives: as the enzyme synthesizing Ca2+-mobilizing second messenger, starting from NAD+, and as the major NAD+-consumer, to be inhibited to increase NAD+ levels. Indeed, the regulation of NAD+ availability is a key event during different processes. In this review, we examine the recent studies related to the modulation of CD38 expression and activity, and the consequent changes in NAD(P)(H), in adipose tissue, during inflammation and cold-induced thermogenesis.